2018
DOI: 10.1016/j.freeradbiomed.2018.04.570
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of cytarabine (Ara-C) in dorsal root ganglion neurons originates from impediment of mtDNA synthesis and compromise of mitochondrial function

Abstract: Peripheral Nervous System (PNS) neurotoxicity caused by cancer drugs hinders attainment of chemotherapy goals. Due to leakiness of the blood nerve barrier, circulating chemotherapeutic drugs reach PNS neurons and adversely affect their function. Chemotherapeutic drugs are designed to target dividing cancer cells and mechanisms underlying their toxicity in postmitotic neurons remain to be fully clarified. The objective of this work was to elucidate progression of events triggered by antimitotic drugs in postmit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 72 publications
1
23
0
Order By: Relevance
“…In contrast, we do not observe any Polδ-catalyzed base incorporation opposite the template AraC residue, similar to that is observed with other high-fidelity polymerases 16,18,29,30 . Thus, on the unmodified template in the presence of all dNTPs, Polδ extends ~44% of the primer strands (Fig.…”
Section: Resultssupporting
confidence: 89%
“…In contrast, we do not observe any Polδ-catalyzed base incorporation opposite the template AraC residue, similar to that is observed with other high-fidelity polymerases 16,18,29,30 . Thus, on the unmodified template in the presence of all dNTPs, Polδ extends ~44% of the primer strands (Fig.…”
Section: Resultssupporting
confidence: 89%
“…This study suggests that cytarabine neurotoxicity in neurons originates in mitochondria and continuous with oxidative stress [10]. Also, IFOS, a structural analog of cyclophosphamide, is an alkylating chemotherapy agent used for a wide range of solid and hematologic malignancies [10]. IFOS has been reported to have adverse neurological effects [11].…”
Section: Introductionmentioning
confidence: 94%
“…A recent study showed that cytarabine inhibits DNA polymerase γ and leads to reduction in mitochondrial DNA (mtDNA) content, ROS generation and oxidative damage in neurons. This study suggests that cytarabine neurotoxicity in neurons originates in mitochondria and continuous with oxidative stress [10]. Also, IFOS, a structural analog of cyclophosphamide, is an alkylating chemotherapy agent used for a wide range of solid and hematologic malignancies [10].…”
Section: Introductionmentioning
confidence: 96%
“…6). Cultures challenged with drugs under normoxic and hypoxic conditions were processed in parallel and XF24‐implemented sequential additions of mitochondrial effectors, oligomycin, FCCP, 2‐deoxyglucose (2DG), and antimycin A, served to determine the treatments signatures on respiratory parameters, as we previously described [16,26]. Under normoxic conditions, baseline OCR in YUMM1.7 was ~ 30% lower compared to B16F10 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Oxygen consumption rates (OCR) were measured using XF24 extracellular flux analyzer (Seahorse, Agilent, Folsom, CA, USA) according to established protocols [23–25] and as we described [16,21,26]. B16F10 and YUMM1.7 cells were seeded in XF24 plates ([0.8‐1.2] × 10 4 /well), grown overnight, and treated as indicated.…”
Section: Methodsmentioning
confidence: 99%